The Synthesis and Characterization of Structural Properties of Hydroxyapatite from Cuttlefish Shell Using X-Ray Diffraction Method - Sitti; Jumardin Jumardin; Nurul Fuadi (Pendidikan Fisika UIN Alauddin Makassar, 2024)
The preparation of solid hydroxyapatite (HAp) with variations in calcination temperature has been carried out. This study aims to determine the crystal size, dislocation density and crystallinity levels of HAp using XRD. HAp is made by mixing cuttlefish shell powder with a solution of KH2PO4, NaOH and Aquades then drying it for 24 hours. Extraction of CaCO3 from cuttlefish shells using the calcination method at various temperature variations, namely 600 0C, 800 0C and 1,000 0C. XRD test to determine the crystal size value, crystal defects and crystallinity of HAp material. XRD data shows that HAp solids form crystals with smaller sizes (50.97 nm, 48.64 nm and 36.52 nm) when the calcination temperature increases, dislocation density increase (0.38 nm-2.10-4, 0.42 nm-2.10-4 and 0.74 nm-2.10-4) as the calcination temperature increases and the crystallinity value decreases (46.31%, 39.06% and 37.93%) based on changes in calcination temperature.